STRATEGI PEMASARAN DAN SOSIALISASI PRODUK BANK WAQAF MIKRO KEPADA MASYARAKAT PESANTREN - Fikri Ali Zen; Ricky Efendy; Abdillah Ubaidi; Romli Muar (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to analyze effective marketing and outreach strategies to raise awareness and interest in micro waqf bank products among small communities. The research utilized a qualitative approach with a case study at An-Nur II Sharia Micro Waqf Bank. Data was gathered through in-depth interviews, field observations, and document analysis. The findings of the study indicate that successful marketing strategies involve personalized approaches, collaboration with local communities, and the use of digital media. In addition, outreach activities that provide education on the concept of waqf and sharia finance have been shown to improve understanding and interest in micro waqf bank products among small communities. This research provides practical insights for micro waqf banks to develop marketing and outreach strategies tailored to the needs of small communities, which are their primary target market.